Personal protective equipment compliance among laundry workers in secondary and tertiary health facilities in Nigeria - Omoijiade, Emmanuel N.; Evbuomwan, Lucky (International Journal Of Community Medicine And Public Health, 2019)
Background: Generally, personal protective equipment (PPE) should be used by healthcare workers, as they provide a physical barrier between hazards and the wearer. Exposure to occupational hazards in the laundry can be limited by the use of PPE such as barrier gowns, gloves, eyewear, foot coverings and face masks. This study provides information on the PPE compliance of the workers at the laundry, as this would prove useful in order to establish appropriate interventions to minimize occupational risks of workers in the healthcare laundries. Methods: This study was a comparative cross-sectional study. It was conducted in six hospitals with a laundry department in Benin-city, composed of one available tertiary healthcare facility and five secondary healthcare facilities. Questionnaire was administered to the workers concerning the availability and use of PPE. Results: The common PPE used were nose masks (7.9%), hand gloves (39.5%), safety boots (3.6%) and coveralls (84.5%). Respondents revealed that eye goggles or face shields and ear plugs or muffs were never provided for them. Conclusions: Compliance of respondents to PPE was not at an optimally recommended level. It is recommended that efforts be made to ensure that workers comply with PPE use, while providing all necessary protective equipment, which should first be assessed before selection and use.